Pathyadi Bidalaka in Management of Vataja Abhishyanda (International Journal of Ayurveda and Pharma Research, 2025)
Vataja Abhishyanda is one of the most common eye disorders affecting people of all ages due to allergens like dust, pollen from trees and grass, animal dander, chemical scents, cosmetic products etc. It is observed to be a seasonal disease, i.e. during summer and spring. It can be correlated with allergic conjunctivitis according to their signs and symptoms. Abhishyanda (conjunctivitis) is the main cause of most eye disorders and must be treated early in effective ways as possible otherwise it may lead to severe complications making the disease unmanageable and would be very difficult to save the eyesight. Allergic conjunctivitis has symptoms like itching, burning sensation, watery, stringy discharge, mild photophobia, and eye congestion. Modern medicine treats it by administering eye drops and anti-allergic drugs, which may have some adverse effects. Ayurvedic management of allergic conjunctivitis has shown some effective results in overcoming the disease with no such effects. According to Acharya Sharangdhara, Pathyadi Bidalaka was done on the patient, who had symptoms of Vataja Abhishyanda (Allergic Conjunctivitis) for 7 days. Vata is said to be the predominant Dosha of Vataja Abhishyanda, Pathyadi Bidalaka has Vataghna properties (pacify Vata Dosha); thus, will reduce the symptoms. The assessment of the condition was done before and after treatment.